ANALISIS NON PERFORMING LOAN TERHADAP RETURN ON ASSET PADA BANK MANDIRI PERIODE 2007-2012 - Sofyan Marwansyah; Rani Kurniasari (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2014)
The banking industry is an important sector in the national development that serves as a financial intermediary between parties who have surplus funds to those who need funds. Factors that affect the profitability of the bank can be sourced from a variety of performance indicators indicated profitability . Important profitability ratio for banks is Return On Assets (ROA). ROA is important for banks because ROA is used to measure the company's effectiveness in generating profits by exploiting its assets. ROA is the ratio of profit before tax to total assets. The larger the ROA shows the better performance of the company, because the level of return the greater. In this study the authors wanted to see whether there is a relationship between the NPL on ROA and whether there is influence between NPL on ROA at Bank Mandiri period from 2006 to 2012, the discussion of the results obtained that the variable NPL (Non Performing Loan) has a relationship to the ROA of -0.906, this shows that the NPL has strong relationships and the opposite direction on ROA, ROA variables significantly influenced by variables NPL (Non Performing Loan) of 82.05 % , while the remaining 17.95 % is influenced by other factors and views of the regression equation obtained for Y = 3.48 to 0.95 X , this shows that if there is no value then the value of ROA will NPLs amounted to 348 , if the value of NPLs increase by 1 unit , then it will reduce the value of ROA of 0.95 units Keyword: Analysis of Non-performing loan, ROA